2005
DOI: 10.1002/ejoc.200500175
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Bisphthalocyanine and Its Nonlinear Optical Properties

Abstract: The synthesis and the nonlinear optical properties of an axially substituted binuclear InCl/InCl phthalocyanine 1 with an unsymmetrical substitution pattern are described. The preparation of this new type of binuclear phthalocyanine has been carried out through a multi-step synthetic strategy, which was specially developed for binuclear phthalocyanines. The study has been carried out with the aim of analyzing which variations of the electronic properties accompany the unsymmetrical extension of the π-electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 69 publications
2
34
0
Order By: Relevance
“…It is found that the spectrum of the sandwich-type complexes displays typical features of the monomeric metal phthalocyanine with a strong Q band at around 670e685 nm and a medium Soret band at about 341 nm. This result indicates that the two Pc rings in the tripledecker complexes show an almost independent behavior [35]. The erbium ion was found to have little effect on the absorption spectra expect for a small split component of the Q-band.…”
Section: Uvevis Absorption Spectramentioning
confidence: 93%
See 1 more Smart Citation
“…It is found that the spectrum of the sandwich-type complexes displays typical features of the monomeric metal phthalocyanine with a strong Q band at around 670e685 nm and a medium Soret band at about 341 nm. This result indicates that the two Pc rings in the tripledecker complexes show an almost independent behavior [35]. The erbium ion was found to have little effect on the absorption spectra expect for a small split component of the Q-band.…”
Section: Uvevis Absorption Spectramentioning
confidence: 93%
“…It is well established that the NLO response of phthalocyanine molecules is originated from a lot of structure factors [3]. And it has been suggested that sandwich-type lanthanide phthalocyanine complexes show improved optical nonlinearities due to their expanded p-electron system and the presence of the heavy lanthanide central metal [17e19, 21,24,26,35,37,38]. Compared to sandwich tripledecker analogs with holmium atom, the erbium complexes exhibit superior NLO response, which indicates that the lanthanide ion plays a more important role in determining the optical nonlinearity of the sandwich type complexes.…”
Section: Nonlinear Optical Propertymentioning
confidence: 99%
“…Hanack et al have recently reported on the OL properties of fused binuclear In III phthalocyaninates, which showed lower performance than their monomeric counterpartners. [14] However, we have described the preparation and Z-scan measurements of highly conjugated ethynyl-and butadyinyl-bridged bis(phthalocyanines) containing Zn II and Co II cation; [15] these compounds have shown moderate cross-section ratios, but higher than the model monomeric phthalocyanines. For this reason, it is our aim to include electron-donor substituents at the periphery and heavy metal atoms in the central cavities of these binuclear structures, since this approach could render very efficient OL materials.…”
Section: Introductionmentioning
confidence: 99%
“…Since their discovery, Pcs have attracted attention as functional chromophores for various applications such as liquid crystals, chemical sensors, electrochromic compounds, and nonlinear optical and photovoltaic cells [2][3][4][5][6][7] . The physicochemical properties of Pcs depend on the nature of the peripheral or nonperipheral functional groups, as well as the electronic properties of the central metal cations in the Pc core 8 .…”
Section: Introductionmentioning
confidence: 99%